2022
DOI: 10.1088/1748-9326/ac59a9
|View full text |Cite
|
Sign up to set email alerts
|

From legacy contamination to watershed systems science: a review of scientific insights and technologies developed through DOE-supported research in water and energy security

Abstract: Water resources, including groundwater and prominent rivers worldwide, are under duress because of excessive contaminant and nutrient loads. To help mitigate this problem, the United States Department of Energy (DOE) has supported research since the late 1980s to improve our fundamental knowledge of processes that could be used to help clean up challenging subsurface problems. Problems of interest have included subsurface radioactive waste, heavy metals, and metalloids (e.g., uranium, mercury, arsenic). Resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 403 publications
0
12
0
Order By: Relevance
“…Globally, U is considered a key environmental contaminant, prevalent in the sub-surface at numerous nuclear legacy and mining sites (e.g., Hanford/Rifle/Oak Ridge, USA). U is also significant in higher activity radioactive wastes that are destined for disposal in a deep underground geological disposal facility (GDF) . To aid long-term containment, any GDF design will contain multiple barriers to limit radionuclide migration from the facility over geological timescales. ,, In addition to naturally occurring minerals from the surrounding host rock of the GDF, the corrosion of engineering iron and steel structures will lead to iron (oxyhydr)­oxide phases (e.g., magnetite, goethite, and green rust) being ubiquitous in and around the facility. Previous studies have shown that iron (oxyhydr)­oxides can readily incorporate U species into their crystal structure and may therefore act as a further barrier to U migration in the environment over timescales relevant to a GDF. However, the sub-surface biogeochemistry of both contaminated land and GDF environments will evolve over time, and this may include redox cycling induced by the onset of sulfate-reducing conditions and/or by oxygen ingress. , Consequently, U-associated iron (oxyhydr)­oxide phases may react with aqueous sulfide via a sulfidation reaction. , Potential reoxidation of this sulfidized system may then occur over the longer term, with cycling likely between reduced and oxidized states. , Given the potential for these fluctuating biogeochemical cycles in the sub-surface (e.g., effects of redox cycling, organic matter, carbonates, etc), , the long-term fate of incorporated radionuclides (including U) is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Globally, U is considered a key environmental contaminant, prevalent in the sub-surface at numerous nuclear legacy and mining sites (e.g., Hanford/Rifle/Oak Ridge, USA). U is also significant in higher activity radioactive wastes that are destined for disposal in a deep underground geological disposal facility (GDF) . To aid long-term containment, any GDF design will contain multiple barriers to limit radionuclide migration from the facility over geological timescales. ,, In addition to naturally occurring minerals from the surrounding host rock of the GDF, the corrosion of engineering iron and steel structures will lead to iron (oxyhydr)­oxide phases (e.g., magnetite, goethite, and green rust) being ubiquitous in and around the facility. Previous studies have shown that iron (oxyhydr)­oxides can readily incorporate U species into their crystal structure and may therefore act as a further barrier to U migration in the environment over timescales relevant to a GDF. However, the sub-surface biogeochemistry of both contaminated land and GDF environments will evolve over time, and this may include redox cycling induced by the onset of sulfate-reducing conditions and/or by oxygen ingress. , Consequently, U-associated iron (oxyhydr)­oxide phases may react with aqueous sulfide via a sulfidation reaction. , Potential reoxidation of this sulfidized system may then occur over the longer term, with cycling likely between reduced and oxidized states. , Given the potential for these fluctuating biogeochemical cycles in the sub-surface (e.g., effects of redox cycling, organic matter, carbonates, etc), , the long-term fate of incorporated radionuclides (including U) is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Spent fuel reprocessing, nuclear waste management, and risk assessment studies over the past few decades have resulted in a large body of literature on plutonium and minor actinide chemistry with aqueous chelators, for both inorganic and organic molecules. [6][7][8][9]11,43 Several speciation studies have been performed to determine the stoichiometry, formation constants, and spectroscopic signatures of actinide complexes, including those with Am(III) and Cm(III). These studies include soluble complexes formed with carbonate-bicarbonate ions, 44−46 phosphates, 47,48 chlorides, small natural chelators like carboxylic acids, 49,50 ATP, 51 hydroxamic acids, 52,53 siderophore ligands, 54−56 humic and fulvic acids, 57−62 and also unidentified natural dissolved organic matter.…”
Section: ■ Introductionmentioning
confidence: 99%
“…While the waste packages are designed to initially isolate the radioactive materials when they are the most radioactive, those engineered barriers will ultimately fail due to underground mechanical forces and natural alteration processes. In this context, contact between radionuclides and the underground natural environment (e.g., minerals, groundwater, metal chelators, as well as microorganisms) is expected to take place, and thus, studying the chemistry of radioelements under environmentally relevant conditions is critical to assess the long-term behavior of nuclear waste. …”
Section: Introductionmentioning
confidence: 99%
“…Here we begin to address this knowledge gap by asking the question: How and to what extent do subsurface carbon transformation, chemical weathering, and solute export differ across hydrological and subsurface structure regimes? To answer this question, we draw upon the rich foundation of reactive transport modeling (RTM) that has been widely used to understand hydrological and biogeochemical coupling (Ackerer et al., 2021; Dwivedi et al., 2022; Jung & Navarre‐Sitchler, 2018; Li, Bao, et al., 2017; Wen et al., 2020). Here we first developed a hillslope‐scale RTM using soil CO 2 and soil water chemistry data from the Fitch Forest, a temperate forest at the ecotone boundary of the Eastern temperate forest and mid‐continent grasslands in Kansas (Fitch, 2006).…”
Section: Introductionmentioning
confidence: 99%